(untitled) (Bioagro, 2024)
The growth and development of the Solanum lycopersicum “tomato” crops is affected by salinity. The objective of the research was to determine the effect of rhizospheric bacteria of Prosopis limensis Benth. "carob" on the development of tomato under salinity. The approach was quantitative and the experimental design completely randomized with four treatments: control (non-inoculated, T1), chemical control with 180 kg·ha-1 N, 100 kg·ha-1 P, 120 kg·ha-1 K (T2), and two treatments of bacteria with 1-aminocyclopropane-1-carboxylate (ACC) deaminase enzyme activity (T3, T4) at 108 cel·mL-1. These were isolated from the rhizospheric soil of 37 carob trees and those with ACCD activity were selected. The two bacteria with the greatest increase on seed germination of an indicator plant (radish) irrigated with saline water (80mM NaCl) were inoculated on tomato cv. Rio Grande seeds and roots before transplanting in a substrate with electrical conductivity of 10.28 dS·m-1. In the rhizosphere of carob trees, 388 Gram-positive (72.16 %) and Gram-negative (27.84 %) bacteria were isolated. The 4.12 % showed ACCD activity and achieved from 89.72 to 100 % germination of radish seeds compared to 32.75 % in the non-inoculated seeds, in saline conditions. Bacillus spp. promoting germination rates of 34.66 and 33.0 day-1 versus 32.11 day-1 in the non-inoculated seeds in non-saline conditions, and 12.29 day-1 in the non-inoculated seeds in saline conditions were identified and selected. These bacteria increased the height, chlorophyll content, potassium/sodium ratio, number and fruit weight of tomato plants compared to the control. It was concluded that Bacillus spp. can constitute biofertilizers to favor tomato cultivation under salinity.